PENYEDIAAN AKSESIBILITAS BAGI WISATAWAN PENYANDANG DISABILITAS OLEH STAKEHOLDER DI KOTAMADYA DENPASAR KECAMATAN DENPASAR SELATAN - Simanjuntak, Carolina; Leli Kusuma Dewi, Luh Gede; Susrami Dewi, Ni Gusti Ayu (Jurnal IPTA (Industri Perjalanan Wisata), 2018)
The purpose of this study is to determine the forms of provision and constraints experienced by stakeholders to provide accessibility for tourists with disabilities in the Denpasar City, South Denpasar District. The informant in this research use purposive sampling method. This research uses descriptive qualitative method, obtained by conducting interview, observation, documentation, and checklist to stakeholder which is divided into three, government, society, and tourism industry. The result of this research is the provision of accessibility for tourists with disabilities by tourism stakeholders in Denpasar City South Denpasar District not yet fully available. The provision of accessibility for tourists with disabilities by tourism stakeholders in Denpasar City, South Denpasar are form of physical accessibility of ram and sliding door while the form of non-physical accessibility are the availability of special services and regulations on the activities of people with disabilities. While the constraints faced by tourism stakeholders in Denpasar City, South Denpasar District in providing accessibility for tourists with disabilities are internal constraints, limited budget and external constraints, regulations that have not specifically regulated the needs of disabled tourists. Suggestion of this research is that among the tourism stakeholder could inisiate, change mindset, and work together in provision accessibility for tourist with disability.